ESG Integration in Financial Accounting: Comparative Evidence and Policy Implications - Andika, Cruift (Yayasan Sinergi Kawula Muda, 2025)
The integration of Environmental, Social, and Governance (ESG) reporting into financial accounting has accelerated as stakeholders demand greater transparency and accountability. This study synthesizes evolving trends, challenges, and policy implications of ESG disclosure, emphasizing its comparative and interdisciplinary contributions. Using a narrative review approach, literature from Scopus, Web of Science, and Google Scholar was analyzed through targeted keywords such as ESG reporting, sustainability accounting, financial performance, and regulatory frameworks. Only peer-reviewed studies from the past decade with financial relevance were included. The review identifies four major themes: (1) standardization and frameworks, (2) technology and innovation, (3) sectoral and regional perspectives, and (4) financial performance and market impact. A conceptual model was developed to illustrate the relationships among these themes. Results show that while frameworks such as IFRS S1/S2, GRI, and SASB improve comparability, inconsistencies remain across regions and industries. Technological tools—particularly artificial intelligence and blockchain—offer potential to enhance data integrity and mitigate greenwashing. Sectoral variations highlight the importance of industry-specific approaches, and comparative analyses indicate that developed economies exhibit stronger ESG reporting practices than emerging markets. Empirical evidence reveals a positive association between comprehensive ESG disclosure and improved financial performance, including profitability and investor confidence. The study concludes that advancing standardized reporting, strengthening regulatory enforcement, and fostering interdisciplinary collaboration are essential to bridge current gaps. Overall, ESG integration within financial accounting is pivotal to aligning corporate strategies with sustainability objectives and ensuring long-term economic resilience.